Seroprevalence of Hepatitis B Virus Surface Antigen among Butchers and Slaughtered Cows in Kano Metropolis, Nigeria - Kareem, A. M.; Mohammed, Y.; Rogo, L. D. (UMYU Journal of Microbiology Research)
Hepatitis B Virus is one of the most important human pathogens which present a significant threat to public health. The objectives of this study are to establish evidence of existence of Hepatitis B Virus (HBV) in cows and prevalence of Hepatitis B Surface Antigen (HBsAg) among butchers. A total of 138 human samples (including slaughter house workers and meat sellers) and 138 slaughtered cows’ samples were collected for detection of HBsAg using ELISA. A questionnaire was administered to collect relevant information regarding risk factors. Screened result showed prevalence rate of 11.6% (p< 0.05) among butchers and 10.9% prevalence was detected in slaughtered cows (p<0.05), these were however not statistically significantly different. Occupational practices including hand cuts and sharing of knives were seen to be more common among slaughter house workers than the meat sellers thereby increasing their exposure to hepatitis B virus infection. It is concluded that both cows and butchers in Kano metropolis serve as reservoir for Hepatitis B Virus and hence there is need for urgent policy formulation (screening and use of protective clothing) in slaughter houses in Nigeria.